2019
DOI: 10.1039/c9lc00508k
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of driftless preconcentration using ion concentration polarization leveraged by convection and diffusion

Abstract: A nanoelectrokinetic study reveals that the Peclet number determines the shape of preconcentrated analytes, as either plug or dumbbell shaped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…demonstrated the abnormal shape of preconcentrated samples (plug or dumb‐bell shape) by DNA experiments of different lengths. The results showed that this will provide new insights into the basic electrodynamic dynamics of molecules in the ICP platform …”
Section: Applications Of Ion Transport Based On Icpmentioning
confidence: 99%
“…demonstrated the abnormal shape of preconcentrated samples (plug or dumb‐bell shape) by DNA experiments of different lengths. The results showed that this will provide new insights into the basic electrodynamic dynamics of molecules in the ICP platform …”
Section: Applications Of Ion Transport Based On Icpmentioning
confidence: 99%
“…Recently, separation and preconcentration of biomolecules has been demonstrated with paper-based ion concentration polarization (ICP) platform. Since conventional ICP preconcentration method has several benefits such as high preconcentration factor and no need of complex buffer exchange, ICP has been extensively studied for the selective preconcentration of biomolecules [8][9][10][11][12]. However, because typical ICP platform required an external electrical field for performing the separation, paper-based ICP separator also needed an external power source and cause the methods to be against to the original concept of μPADs.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] The electric field gradient associated with ICP has also been used for dielectrophoresis of cells, [14,28,29] salt water desalination, [17,[30][31][32] and analyte enrichment. [33] Analytes such as charged fluorophores, [1,34,35] microparticles, [23,36] and proteins [37,38] have all been enriched, with up to a million-fold enrichment factor in one case. [16] A few years ago, our group introduced an electrochemical variant of ICP called faradaic ICP (fICP).…”
Section: Introductionmentioning
confidence: 99%
“…The electric field gradient associated with ICP has also been used for dielectrophoresis of cells, salt water desalination, and analyte enrichment . Analytes such as charged fluorophores, microparticles, and proteins have all been enriched, with up to a million‐fold enrichment factor in one case …”
Section: Introductionmentioning
confidence: 99%